miRNA-98-5p Targeting IGF2BP1 Induces Mesenchymal Stem Cell Apoptosis by Modulating PI3K/Akt and p53 in Immune Thrombocytopenia - Yanan Wang; Jiamin Zhang; Yan Su; Chencong Wang; Gaochao Zhang; Xiao Liu; Qi Chen; Meng Lv; Yingjun Chang; Jun Peng; Ming Hou; Xiaojun Huang; et al. (Elsevier, 2020)
Immune thrombocytopenia (ITP) is a common hematological autoimmune disease, in which defective mesenchymal stem cells (MSCs) are potentially involved. Our previous study suggested that MSCs in ITP patients displayed enhanced apoptosis. MicroRNAs (miRNAs) play important roles in ITP by affecting megakaryopoiesis, platelet production and immunoregulation, whereas the roles of miRNAs in ITP-MSCs remain unknown. In a previous study, we performed microarray analysis to obtain mRNA and miRNA profiles of ITP-MSCs. In the present study, we reanalyze the data and identify miR-98-5p as a candidate miRNA contributing to MSC deficiency in ITP. miR-98-5p acts through targeting insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1), and the subsequent downregulation of insulin-like growth factor 2 (IGF-2) causes inhibition of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, which is involved in the process of MSC deficiency. Furthermore, miR-98-5p upregulates p53 by inhibiting β-transducin repeat-containing protein (β-TrCP)-dependent p53 ubiquitination. Moreover, miR-98-5p overexpression impairs the therapeutic effect of MSCs in ITP mice. All-trans retinoic acid (ATRA) protects MSCs from apoptosis by downregulating miR-98-5p, thus providing a potential therapeutic approach for ITP. Our findings demonstrate that miR-98-5p is a critical regulator of ITP-MSCs, which will help us thoroughly understand the pathogenesis of ITP.